Redundancy in Highway Bridges - Frangopol, Dan M.; Nakib, Rachid (Engineering Journal, 1991)
The present study primarily reviews definitions of deterministic and probabilistic system redundancy measures which could be used in the design and evaluation of highway bridges. Some of these measures are used to evaluate the redundancy of an existing steel girder bridge. In this context, corrosion and accidental damages are simulated and the bridge redundancy is evaluated by using three-dimensional nonlinear finite element and probabilistic system analyses. The bridge damage-redundancy-reliability interaction is also studied.